Local Peoples’ Perspectives on Religious Tourism: A Research in Demre District of Antalya - Aksu, Akin; Oksuz, Emine Nurdan (Journal of Tourism Management Research, 2021)
Like other industries, tourism and travel industry has been affected too much from global COVID-19 pandemic. The negative effects of pandemic can be easily seen in all tourism types starting from 3S (sea, sand, sun) tourism to religious tourism. According to World Religious Travel Association (WRTA) around 300 million tourists move internationally in religious tourism market. This study aimed to determine the perspectives of the local people living in Demre on religious tourism and to find out whether the local people living in the district were aware of the potential of religious tourism in the district. It also aimed to reveal whether there was a difference between the demographic characteristics of the local people and their perspectives on religious tourism. As a result of the logistic regression analysis conducted within the scope of the research, it was observed that people with high income levels and those working as managers had a low perspective on religious tourism.